(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
In recent years, consistent priority has been given in our country to reforms aimed at fundamentally transforming the activities of higher education institutions, increasing their scientific potential, improving the quality of education, and expanding the coverage of the population with higher education services. It is necessary to focus on the essence of the economic category of “innovative higher education.” Based on the results of our research, the following author’s definition of this economic category has been developed: “Innovative higher education is an educational process carried out by higher education institutions possessing modern innovative infrastructure, which, by continuously taking into account internal and external factors influencing the structure of the higher education services market, enables the development of individuals through improving the quality of independent learning of its participants, including students, and the formation of high-quality professional competence.”